Comparing the embodied carbon and cost of concrete floor solutions. (15th November 2021) - Jayasinghe, Amila; Orr, John; Ibell, Tim; Boshoff, William P.
Abstract: Multi-objective optimisation of concrete floors for economic and environmental performance is critical in the present context since the building construction sector is responsible for a rising share of the global economy and greenhouse gas emissions. This study explores how the designs with optimum cost and embodied carbon are governed by the selection of a concrete floor system and column spacing. Discrete concrete floor designs were generated parametrically varying the column spacing for eight different construction forms available in practice. Pareto optimal solutions for cost and cradle-to-gate embodied carbon were identified for a range of column spacings. The trends of the sensitivity of the optimum solutions were also investigated due to inherent uncertainty and potential variations in the cost and embodied carbon of different constituents. Column spacings can be increased up to 2 m than the optimum, compromising cost or embodied carbon only up to 10% due to their nonlinear relationship, depending on the slab type. Post-tensioning can reduce embodied carbon of flat slabs for spans longer than 7 m but do not reach Pareto optimality due to available cheaper floor solutions with similar levels of embodied carbon. Flat slabs can be suggested as Pareto optimal for spans within 6 m–8 m when construction time and storey height is considered, due to reduced cost. However, parallelly Pareto optimal two-way slabs on beams have up to only 8% higher cost but up to 37% lower embodied carbon than flat slabs. While the floor designs are optimum for spans within 5–7 m for most of the slab types, two-way slabs on beams and/or hollow-core slabs are the optimum choice for a wide range of spans depending on relevant cost and carbon coefficients.